Penerapan Struktur Tiga Babak Dalam Penulisan Naskah Film Dokumenter “Belongings Through Lines” Tentang Komunitas Bandung Sketchwalk - Samir, Sabila; Wirakusumah, Teddy Kurnia; Risanti, Yuliana Dewi (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik USB YPKP, 2025)
The development of communication technology has given rise nowaday. The documentary Belongings Through Lines seeks to portray the dynamics of this community using a three-act narrative structure, highlighting personal stories, challenges, and reflections on their role in preserving the city’s collective memory through sketching. This study aims to explain the stages of Act I (Set Up), Act II (Confrontation), and Act III (Resolution) in the scriptwriting of the documentary Belongings Through Lines. The results show: 1) Act I introduces the Bandung Sketchwalk community, the values of urban sketching, and the cultural and emotional background through intimate and reflective audio-visual elements; 2) Act II presents the conflict of maintaining the community, as well as the members’ motivations and social dynamics through interviews and the 100th sketchwalk event; 3) Act III offers a narrative reflection on the meaning of the Bandung Sketchwalk community’s continuity and the values sustained over the past decade.